Towards a decentralized planning policy in Iraq (Journal of Planner and Development, 2007)
Iraq is changing from the centralized system of governance to the decentralized system, which assumes devolution of more authorities to the local governments of Iraqi provinces and cities. This puts a responsibility on the academics to produce more research work on the best framework for this change, to ensure the best results. The main objective of this research is to suggest a policy for the decentralized transformation in domain of Urban and Regional Planning in Iraq. A suggested program for the transformation is involved in the paper as well, with analysis for the new relationships between different levels of planning authorities depending on democracy. In addition, a description for planning process flows from bottom to top.